STEAM Based Loose Parts Learning for Enhancing Early Childhood Creativity at TK Nurul Qur’ Stabat - Asmidar Parapat; Munisa; Rita Nofianti; Saputri Wulandari (Yayasan Multidimensi Kreatif, 2025)
This community engagement program aimed to enhance early childhood creativity through the implementation of STEAM-based loose parts learning at TK Nurul Qur'an Stabat. The background of this initiative stems from the limited teacher understanding of STEAM pedagogy and the underutilization of loose parts as open-ended materials that can stimulate children's creativity, problem-solving, and exploration skills. The program involved several stages, including preliminary observation, workshop-based socialization, hands-on practice, and evaluation. Teachers participated in discussions, demonstrations, and collaborative activities to design STEAM-integrated learning using affordable and flexible loose parts. The results show a significant increase in teachers’ conceptual understanding and practical skills in designing creative learning experiences, as well as greater awareness of their role as facilitators rather than instructors. Teachers were able to develop STEAM-based activities that encouraged children’s imagination, experimentation, collaboration, and creativity. The program concludes that STEAM-based loose parts learning is an effective approach to improving the quality of early childhood education and can be sustainably implemented with continuous teacher support and innovation.